ANALISIS FAKTOR YANG MEMPENGARUHI KUALITAS HASIL AUDIT (STUDI EMPIRIS PADA KANTOR AKUNTAN PUBLIK DI PEKANBARU) - Asrini, Widya Asrini; Syahza, Almasdi Syahza; ', Makhdalena (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study was conducted to examine the effect of Competence, Independence, Objectivity and Due Professional Care for Quality Audit. The population used in this study there are 59 auditors, type of data used is qualitative data sourced from the auditor. Data analysis technique using multiple linear analysis, t test and f test with significance level of 0.10%.The result showed that the Competence, Independence, Objectivity and Due Professional Care simultaneously affect the Quality Audit. Based on the partial results of the study showed a positive effect on the Quality Competence Audit, Independence positive effect on the Quality Audit, Due Professional Care negatively affect the quality of audit results, meanwhile Objectivity does not affect the quality of audit results. The coefficient of determination shows that the Competence, Independence, Objectivity, and Due Professional Care Quality Audit affect 90.1% and the remaining 9.9% are not described in this research mode. Keywords: Quality Audit, Competence, Independence, Objectivity and Due Professional Care